2009
DOI: 10.1007/s12237-009-9148-x
|View full text |Cite
|
Sign up to set email alerts
|

Oyster and Macroalgae Bioindicators Detect Elevated δ15N in Maryland’s Coastal Bays

Abstract: Nitrogen loading from anthropogenic sources, including fertilizer, manure, and sewage effluents, has been linked with declining water quality in coastal lagoons worldwide. Freshwater inputs to mid-Atlantic coastal lagoons of the USA are from terrestrially influenced sources: groundwater and overland flow via streams and agricultural ditches, with occasional precipitation events. Stable nitrogen isotopes ratios (δ 15 N) in bioindicator species combined with conventional water quality monitoring were used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…The δ 15 N values in macroalgae have often been related to δ 15 N in DIN sources (e.g., Costanzo et al 2001;Cole et al 2004;Cohen and Fong 2006;Dillon and Chanton 2008;Oczkowski et al 2008;Fertig et al 2009). Although phytoplankton fractionate nitrate (NO 3 − ) during uptake and assimilation, with 14 NO 3 − reacting faster than 15 NO 3 − , macroalgae do not (Dillon and Chanton 2008 (Karsh et al 2003;Needoba et al 2003).…”
Section: Discussion δ 15 N In Macroalgae and Oystersmentioning
confidence: 99%
“…The δ 15 N values in macroalgae have often been related to δ 15 N in DIN sources (e.g., Costanzo et al 2001;Cole et al 2004;Cohen and Fong 2006;Dillon and Chanton 2008;Oczkowski et al 2008;Fertig et al 2009). Although phytoplankton fractionate nitrate (NO 3 − ) during uptake and assimilation, with 14 NO 3 − reacting faster than 15 NO 3 − , macroalgae do not (Dillon and Chanton 2008 (Karsh et al 2003;Needoba et al 2003).…”
Section: Discussion δ 15 N In Macroalgae and Oystersmentioning
confidence: 99%
“…Although a variety of isotopic studies deal with riverine inflow into estuarine and coastal environments (e.g. Rogers 2003, Fertig et al 2009), most of them are aimed at detecting anthropogenic sources, such as sewage inflows, which can be distinguished from unpolluted marine sources via their δ 15 N values (Heaton 1986, Costanzo et al 2001 (Hill & McQuaid 2008). Even coastal areas with relatively high anthropogenic influence show a predominance of phytoplanktonic organic matter in the food of benthic filter feeders (Page & Lastra 2003).…”
Section: Implications For the C-and N-cyclesmentioning
confidence: 99%
“…Although a variety of isotopic studies deal with riverine inflow into estuarine and coastal environments (e.g. Rogers 2003, Fertig et al 2009), most of them are aimed at detecting anthropogenic sources, such as sewage inflows, which can be distinguished from unpolluted marine sources via their δ . Carbon and nitrogen isotope signatures of organisms from an estuarine food web in Plum Island Sound, USA, also exhibited minimal importance of TOM (Deegan & Garritt 1997).…”
mentioning
confidence: 99%
“…Biological indicators such as the δ 15 N of either the zebra mussels (Fry and Allen 2003), or the oyster Crassostrea virginica and the macroalgae Gracilaria sp. (Fertig et al 2009) were suggested to monitor the anthropogenic impact or animal wastes on watershed in aquatic ecosystems. Lefebvre et al (2009a) and Grangeré et al (2012) suggested the use of both δ 13 C and δ 15 N values of the Pacific oyster C. gigas muscle tissue to typify the trophic functioning of coastal ecosystems.…”
Section: Introductionmentioning
confidence: 99%